Student Interest in Mathematics using Routine and Non-Routine Problems in the Rotating Trio Exchange Cooperative Learning Model - Ajeng Gelora Mastuti; Yuli Hastuti; Eni Sartika (Al-Khwarizmi : Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2023)
Abstract:Types of questions and the way the teacher teaches can affect student learning interests. One learning model that can increase students' interest in learning is the Rotating Trio Exchange cooperative learning model. This study examined the differences in students' learning interests using routine vs non-routine questions in the Rotating Trio Exchange cooperative learning model. The type of research used is quasi-experimental, with a sample of 44 junior high school students. The instruments used in this study were fractional material test questions, questionnaires, and observation sheets. Data analysis used a validity test, reliability test, normality test, homogeneity test, Wilcoxon test, and independent sample t-test. This study concluded that there were differences in the average learning interest of students who used routine and non-routine questions in the Rotating Trio Exchange cooperative learning model.Abstrak:Jenis pertanyaan dan cara guru mengajar dapat mempengaruhi minat belajar siswa. Salah satu model pembelajaran yang dapat meningkatkan minat belajar siswa adalah model pembelajaran kooperatif Rotating Trio Exchange. Tujuan penelitian ini adalah melihat perbedaan minat belajar matematika siswa yang menggunakan soal rutin vs non rutin pada model pembelajaran kooperatif tipe Rotating Trio Exchange. Jenis penelitian yang digunakan adalah penelitian Eksperimen Semu dengan jumlah sampel 44 siswa SMP. Instrumen digunakan penelitian ini adalah soal tes materi pecahan, angket dan lembar observasi. Analisis data menggunakan uji validitas, uji reliabitas, uji normalitas, uji homogenitas, uji wilcoxon dan uji independent sampel t-test. Hasil penelitian ini menyimpulkan bahwa terdapat perbedaan rata-rata minat belajar siswa yang menggunakan soal rutin dan non rutin pada model pembelajaran kooperatif tipe Rotating Trio Exchange.